Redeveloping the Congregation: A How to for Lasting Change - Sellon, Mary; Smith, Dan; Grossman, Gail (Rowman & Littlefield Publishers, 2002)
What makes it possible for a church to reverse course from decline or stagnation into longlasting vitality? How can a church immigrate from a congealing present into a compelling future? What can a congregation do to experience continuous, deep change rather than just temporary, surface improvement? How does a person lead redevelopment? The three authors of this book address these and other questions by building on an eight-step framework for lasting change developed by John P. Kotter, noted former professor of organizational behavior at Harvard Business School. His work on organizational change is heralded in the secular world as foundational, and Smith, Sellon, and Grossman have found that his findings hold true for congregations as well. Each chapter in this book comprises three sections: mentor, companion and coach. The mentor section discusses principles and concepts to be addressed in each of the eight steps; the companion section gives readers a sense of what leading change is actually like for a congregational leader; and the coach section provides specific ways for leaders to develop the unique change processes that will be effective in their church. Foreword by Anthony G. Pappas. "The authors offer strong spiritual grounding and wise counsel for personal and communal transformation as they lead us through a highly effective process of congregational transformation." -- Barbara B. Troxell "This book does not offer us more exhausting busyness, but focuses on the very heart of ministry in and through the congregation. If you yearn to move beyond the status quo, dive into this refreshing book and expect transformation." -- Julia Kuhn Wallace